Analisis Kebijakan Pemerintah Daerah Kota Cilegon Dalam Penetapan Desa Wisata Watu Lawang - Fuqoha Fuqoha (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2021)
Agro-tourism is one of the tourist attractions for regional and national tourists. Watu Lawang has potential tourism object to become an agro-tourism that has been determined by Local Tourism and Culture Departement of Cilegon City has not been implemented optimally. The tourism sector, which is designated as the leading sector in increasing the country's economic growth, is a challenge for local governments in optimizing tourism potential. The purpose of developing tourism and regional culture as a tourism destination is a form of increasing foreign exchange for the region in particular and the economy of the local community or region in general. The purpose of this study was to analyze policies, strategies and constraints in the development and development of tourism objects in Watu Lawang agro-tourism in the city of Cilegon. The research method used is descriptive qualitative research and normative juridical approach, data and document collection is done through interviews and observations. The results showed that the tourism policies have been formed from national policies to regional policies. Various strategies have been formulated by the ministry of tourism and the tourism office in the regions in order to develop the potential for tourism objects. The potential of the Watu Lawang agro-tourism object is not optimal due to several factors, including accessibility, facilities, human resources, geographic and sociological location.